Bonjour c'est urgent c'est pour demain!!!!!!!
Réduire les expressions qui peuvent l'être
x²+x²=
x⁵ *x⁵=
x⁵ + x⁵=
x⁵ * x²=
x⁵ + x²=
x + x²=
x² *x=
3x²- x²=
3x² *(-x²)=
3x² - x =
- x -2x =
- x*( - 2x) =
-x² - x² =
- x²* ( -x²) =
- x+ x² =
merci pour votre aide :)

1

Réponses

Meilleure réponse !
2014-05-04T18:39:12+02:00
Bonsoir

x²+x²= 2x²
x⁵ *x⁵= x¹°
x⁵ + x⁵= 2x⁵
x⁵ * x²= x⁷
x⁵ + x²=incalculable
x + x²= incalculable
x² *x= x³
3x²- x²= 2x²
3x² *(-x²)= -3x⁴
3x² - x =incalculable
- x -2x = -3x
- x*( - 2x) = +2x²
-x² - x² = -2x²
- x²* ( -x²) = x⁴
- x+ x² =
incalculable